Computational screening of metal-organic frameworks with open copper sites for hydrogen purification. (16th October 2020) - Chiau Junior, Manuel J.; Wang, Yuguo; Wu, Xuanjun; Cai, Weiquan
Abstract: With the increasing demand for environmental protection worldwide, metal-organic frameworks (MOFs) have been pivotal in the clean energy domain. Due to the high surface areas, large porosities and structural tunability, they are promising for the adsorption separation of H2 /CH4 mixtures. High-throughput computational screening was adopted to identify the optimal adsorbents for hydrogen purification from 502 MOFs with open copper sites. Firstly, the adsorption performance of H2 /CH4 mixture in 440 MOFs, which exhibit non-zero surface area and over -3.8 Å largest cavity diameter (LCD), was calculated using grand canonical Monte Carlo (GCMC) simulations at 300 K and various pressures. Secondly, we identified the top 9 high-performance MOFs by evaluating the ranking of candidate adsorbent performance according to a combination metric of adsorption performance score (APS, the product of adsorption capacity of CH4 and selectivity of CH4 over H2 ) and percent regenerability (R%). PCN-39 and MOF-505 exhibit high APS of 101 mol kg −1 and 67.9 mol kg −1, respectively, promising for hydrogen purification. Subsequently, the breakthrough curves of H2 /CH4 mixture through the fixed bed packed with some optimal MOFs were predicted to evaluate their effects in practical hydrogen purification. UMODEH08 or UMOBEF04 exhibits the long dimensionless residence time over 30 of CH4 for the H2 /CH4 separation. Finally, we also explored the behaviors of the radial distribution functions (RDF) and adsorption equilibrium configurations to further demonstrate how the selected MOFs differentiate CH4 from H2 . The investigation on all these observations at molecular level will pave the way for the development of new materials for clean energy applications. Highlights: Screening 502 MOFs with open copper sites for hydrogen purification. Identification of top nine real MOFs with high-performance for H2 /CH4 separation. Breakthrough predictions for H2 /CH4 mixture in the fixed bed packed with MOFs. Mechanism elucidation of MOFs distinguishing methane from hydrogen.